Concise Review: Understanding the Renal Progenitor Cell Niche In Vivo to Recapitulate Nephrogenesis In Vitro. (22nd October 2015) - Mari, Chiara; Winyard, Paul
Abstract : An overview of the native nephrogenic niche, describing the complex signals that allow survival and maintenance of undifferentiated renal stem/progenitor cells and the stimuli that promote differentiation, is provided. Abstract: : Chronic kidney disease (CKD), defined as progressive kidney damage and a reduction of the glomerular filtration rate, can progress to end-stage renal failure (CKD5), in which kidney function is completely lost. CKD5 requires dialysis or kidney transplantation, which is limited by the shortage of donor organs. The incidence of CKD5 is increasing annually in the Western world, stimulating an urgent need for new therapies to repair injured kidneys. Many efforts are directed toward regenerative medicine, in particular using stem cells to replace nephrons lost during progression to CKD5. In the present review, we provide an overview of the native nephrogenic niche, describing the complex signals that allow survival and maintenance of undifferentiated renal stem/progenitor cells and the stimuli that promote differentiation. Recapitulating in vitro what normally happens in vivo will be beneficial to guide amplification and direct differentiation of stem cells toward functional renal cells for nephron regeneration. Significance: Kidneys perform a plethora of functions essential for life. When their main effector, the nephron, is irreversibly compromised, the only therapeutic choices available are artificial replacement (dialysis) or renal transplantation. Research focusing on alternative treatments includes the use of stem cells. These are immature cells with the potential to mature into renal cells, which could be used to regenerate the kidney. To achieve this aim, many problems must be overcome, such as where to take these cells from, how to obtain enough cells to deliver to patients, and, finally, how to mature stem cells into the cell types normally present in the kidney. In the present report, these questions are discussed. By knowing the factors directing the proliferation and differentiation of renal stem cells normally present in developing kidney, this knowledge can applied to other types of stem cells in the laboratory and use them in the clinic as therapy for the kidney.